Clearance of apoptotic cells: implications in health and disease - Elliott, Michael R. (The Rockefeller University Press, 2010)
Recent advances in defining the molecular signaling pathways that regulate the phagocytosis of apoptotic cells have improved our understanding of this complex and evolutionarily conserved process. Studies in mice and humans suggest that the prompt removal of dying cells is crucial for immune tolerance and tissue homeostasis. Failed or defective clearance has emerged as an important contributing factor to a range of disease processes. This review addresses how specific molecular alterations of engulfment pathways are linked to pathogenic states. A better understanding of the apoptotic cell clearance process in healthy and diseased states could offer new therapeutic strategies.